Chondrosarcoma of hyoid bone: a case report - Dania Syed; Hamdan Pasha; Javaria Parwez Ali; Shakil Aqil (Journal of the Pakistan Medical Association, 2023)
Chondrosarcoma of hyoid bone is a rare malignant tumour, with only a few cases reported in literature. We present the case of a 28-year-old male with grade I hyoid bone chondrosarcoma. Key words: Chondrosarcoma, Hyoid bone, CT scan.